“SI TOU TIMOU TUMOU TOU”: BERTEOLOGI PASTORAL KELUARGA DALAM KONTEKS BUDAYA MINAHASA DI TENGAH PERUBAHAN ZAMAN - Agnes Beatrix Jackline Raintung; Daniel Susanto (POIMEN Jurnal Pastoral Konseling, 2021)
The time has brought changes in all aspects of human life, including family life. Communal relations in families in the East are increasingly being eroded due to the influence of increasingly advanced science and technology. However, eastern cultural values ​​essentially have tremendous wealth for family survival. This study aims to examine the family from the perspective of Minahasa culture as a context for family pastoral theology, especially with regard to the philosophy of life of the Minahasan people, namely Si Tou Timou Tumou Tou which means humans live to bring others to life. The purpose of this study is to describe the philosophy of life of the Minahasa people as a context for family pastoral theology in the midst of changing times. The research methodology used is library research on family pastoral theology and Minahasa culture related to si tou timou tumou tou. The findings are that the life philosophy of the Minahasa people, si tou timou tumou tou is something important and crucial for family life in the midst of today's changes. Families that live to humanize others will be able to survive and continue to grow together in the midst of changing times. The conclusion of this study explains that si tou timou tumou tou is a relevant pastoral theological context for families in the current era of change.